(untitled) (Analele Universității din București - Istorie, 2024)
The present study aims to capture some of the aspects of the relationship between Romanians and Jews, the targeted field being that of education. The school system, an area on which there have been extensive disputes over time, has been used in turn by participants in the training process as a tool for assimilation, discrimination and emancipation. During the period of consolidation of national consciousness, the majority gave shape to the desire to eliminate differences and opened public schools for minorities in order to assimilate them faster. Subsequently, finding shortcomings in the application of the principle of compulsory primary education among Romanians and the overrepresentation of Jews in the public sector, the latter were restricted access to free schooling. The introduction of restrictive provisions for other levels of education was the expression of the radicalization of Romanian society, especially in the twentieth century. On the other hand, these discriminatory measures boosted the opening and development of Jewish schools, and thus the emancipation of the Jewish population.